2017
DOI: 10.1002/adsc.201601388
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Carbonylative C–H Functionalization of 1,2,3‐ Triazoles for the Synthesis of Triazolo[1,5‐a]indolones

Abstract: This study presents a synthesis of 4H-[1,2,3]triazolo[1,5-a]indol-4-ones. The key step in the synthesis of this new heterocyclic scaffold is an intramolecular cyclization via an unprecedented carbonylative C-H functionalization of 1-(2-bromoaryl)-1,2,3-triazoles. Isotopic labeling of the carbonyl carbon atom is possible using near stoichiometric amounts of 13 CO. Additionally, an alternative pathway via carbonylative Sonogashira coupling followed by a two-step one pot azidation/cycloaddition is also investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…carbon monoxide in toluene at 120 °C for 18 hours, gave direct access to triazolo[1,5‐ a ]indolones 86 obtained in good to high yields, ranging from 49 % to 93 % (Scheme ). Probably due to their poor stability, the worst reaction yields, 0 % and 34 %, were obtained when the substituent on the triazole ring of the starting material was the trimethylsilyl or the triisopropylsilyl group, respectively …”
Section: Alternative Sources Of Carbon Monoxide In the Pd‐catalyzementioning
confidence: 99%
See 3 more Smart Citations
“…carbon monoxide in toluene at 120 °C for 18 hours, gave direct access to triazolo[1,5‐ a ]indolones 86 obtained in good to high yields, ranging from 49 % to 93 % (Scheme ). Probably due to their poor stability, the worst reaction yields, 0 % and 34 %, were obtained when the substituent on the triazole ring of the starting material was the trimethylsilyl or the triisopropylsilyl group, respectively …”
Section: Alternative Sources Of Carbon Monoxide In the Pd‐catalyzementioning
confidence: 99%
“…In 2017, a robust CO precursor, based on formic acid, mesyl chloride and triethylamine, was employed for the synthesis of a new heterocyclic scaffold, the triazolo[1,5-a]indolone ring system 86, via a palladium-catalyzed intramolecular carbonylative C-H functionalization of substituted triazoles 85 (Scheme 46). [89] Scheme 46. Intramolecular carbonylative C-H functionalization of 1-(2bromophenyl)-1,2,3-triazoles 85 affording triazolo [1,5-a]indolones 86.…”
Section: Alternative Sources Of Carbon Monoxide In the Pd-catalyzed Smentioning
confidence: 99%
See 2 more Smart Citations
“…Veryser et al reported on a related strategy by using mesyl chloride for activating formic acid instead of acetic anhydride. The CO‐liberation was rapid under the developed conditions and could be generated ex situ by using COware for aminocarbonylations and carbonylative cyclizations, respectively. Representative examples of 13 C‐enriched compounds from these studies are depicted in Scheme 29A ( 110 and 111 ).…”
Section: C‐carbonylation Using [13c]comentioning
confidence: 99%